The influence of agrometeorological conditions and sowing techniques on seed productivity of variegated alfalfa in the Middle Cis-Urals - N. I. Kasatkina; Zh. S. Nelyubina (Аграрная наука Евро-Северо-Востока, 2025)
The aim of the research is to identify the influence of agrometeorological conditions, age of grass stand and sowing techniques (cover crop, sowing method) of variegated alfalfa Victoria on its seed productivity. The research was conducted in 2019–2023 on sod-podzolic medium loamy soil of the Udmurt Republic (Middle Cis-Urals). The meteorological conditions of the growing season in 2023 were characterized by significant dryness according to the hydrothermal coefficient (HTC – 0.63), in 2021 and 2022 – by dryness (HTC – 0.78 and 0.91), in 2020 – by slight dryness (HTC – 1.04) and in 2019 – by waterlogging (HTC – 1.73). The regrowth of alfalfa was noted during the years of research in the 2nd-3rd ten-day period of April; the vegetation period before harvesting the seeds lasted 124–142 days. Over four years of use, alfalfa has generated yields at a rather high level: in the first year of use – 570–759 kg/ha, in subsequent years – 234–309 kg/ha. On average, over the years of research, the highest yields were when alfalfa was sown in a wide–row (60 cm) manner under the cover of spring wheat or a vetch-oat mixture – 360 and 359 kg/ha, respectively. Agrometeorological conditions of the year influenced the yield of the crop (93.3 % of variability) and its structure indicators. In dry years, the height of alfalfa plants (88.5 % of variability) was 74–84 cm, in wetter years – 108–119 cm; the weight of 1000 seeds (84.8 % of variability) was 1.88–2.39 g and 1.57–1.75 g, respectively. With aging of the herbage, the density of seed grass decreased from 289-420 to 192–260 pcs/m2, the number of pods per cluster from 8.6–10.2 to 6.3–8.0 pcs, the number of seeds in a pod (76.1 % of variability) – from 4.3–4.9 to 2.0–2.4 pcs. The number of clusters on a shoot and the number of pods in a cluster had an average positive effect on the level of seed productivity of alfalfa (r = 0.47 and r = 0.53, respectively).